PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V.B SDN 036 SERUSA KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Salbiah '; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted in 036 Serusa SDN VB class Bangko Rokan Hilir subdistrict school year 2013/2014 the number of 24 students, 8 women and 16 men. the background for this study is the low student science learning outcomes. This is evident from the number of students who have not completed. Of the 24 students who achieve only 8 KKM. The shape of this research is Classroom Action Research (CAR), which consists of two cycles with four meetings. This study aims to improve student learning outcomes IPA SDN VB class 036 Serusa Bangko Rokan Hilir subdistrict with the application of problem-based learning model. By using techniques such as data collection sheets and student teacher observation and repeat the cycle end. The results showed an increase in activity of teachers and students. Teacher activity in the first cycle the first meeting with the percentage 75% increase in the second meeting to be 85%, whereas at the first meeting of the second cycle increased from the first cycle to 95% and at the second meeting remains 95%. While the activities of students in the first cycle the first meeting with the percentage of 60% and increased in the second meeting to 70%, while in the second cycle of the first meeting with the percentage of 85% and increased in the second meeting to be 90%. The results of the VB class students learn science SDN 036 Serusa Bangko Rokan Hilir subdistrict with science learning outcomes of students on the basis of scores with an average of 61.2. at the end of the replay after the first cycle of action with an average of 66.1, an increase of 8% from the baseline score, and the end of the second cycle replicates with an average 71.3, an increase of 8% from the first cycle or 17% of the baseline score. It can be concluded that the application of Problem Based Learning Model to Improve Student Learning Outcomes IPA SDN VB Class 036 Serusa Bangko Rokan Hilir Subdistrict second semester in the Academic Year 2013/2014. Keywords: Problem-Based Learning Model, Learning Outcomes IPA